1991
DOI: 10.1002/pssb.2221660109
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Fe Precipitation in Cu97Fe3 and Cu75Au24Fe1

Abstract: A series of isothermal and isochronal heat treatments (300 to 800 °C; 0 to 92 h) is used to compare the precipitation of f.c.c. γ‐Fe in Cu97Fe3 with that in Cu75Au24Fe1 as determined by room temperature Mössbauer spectroscopy. The precipitation process is similar in both systems with up to 90% and 70% of the Fe in Cu97Fe3 and Cu75Au24Fe1, respectively, being precipitated in the form of γ‐Fe. Low temperature measurements (15 K) in zero and applied magnetic fields (5.3 T) on γ‐Fe in the Cu75Au24Fe1 sample show m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The results indicated that the Fe inclusions were in a (high volume) ferromagnetic state, as opposed to a (low volume) antiferromagnetic state. Subsequent Mössbauer results collected for a similar sample, consisting of Fe inclusions in Cu 0.76 Au 0.24 , were, however, contradictory and consistent with a (low volume) low moment state [48].…”
Section: Magnetometrymentioning
confidence: 91%
See 1 more Smart Citation
“…The results indicated that the Fe inclusions were in a (high volume) ferromagnetic state, as opposed to a (low volume) antiferromagnetic state. Subsequent Mössbauer results collected for a similar sample, consisting of Fe inclusions in Cu 0.76 Au 0.24 , were, however, contradictory and consistent with a (low volume) low moment state [48].…”
Section: Magnetometrymentioning
confidence: 91%
“…Indeed, ultra-thin fcc Fe films with increased atomic moments have been grown epitaxially on Cu 1−x Au x substrates [43][44][45][46]. However, while there are also a few accounts of the magnetic behaviour of fcc Fe precipitates in Cu 1−x Au x [47,48], in samples prepared from a melt, the results from these are not in complete agreement with each other and do not always imply high moments [48].…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical indication made the iron fcc structure appealing from the point of view of potential applications. To obtain such a c-Fe phase, several attempts have been made: (i) alloying Fe with other elements such as Ni (like in stainless steel); (ii) epitaxially growing Fe ultra thin films on Cu (Shen et al 1998) or Cu/Si (Gubbiotti et al 1999) substrates; (iii) forming fcc Fe precipitates in Cu (Hines et al 2009) or Cu 1-x Au x (Klein et al 1991) matrix through heat treatments; (iv) synthesizing c-Fe nanoparticles and nanowires on a carbon film (Ling et al 2008(Ling et al , 2009); and (v) very recently embedding iron fcc nanoparticles in carbon nanotubes (CNT) (Lyubutin et al 2012). These last studies are particularly appealing because (i) it is possible to grow highly oriented CNTs, leading to anisotropic magnetic response of the device (Lyubutin et al 2012), and (ii) the surrounding CNT walls protect the metallic nanostructures from the action of ambient oxygen (Camilli et al 2011).…”
Section: Introductionmentioning
confidence: 99%